BAIUL WAFA` (Review Penggunaan Dalil Mashlahah di Kalangan Hanafiyah) - Asaari, Asaari (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2013)
Bai al-Wafa` first appeared in Central Asia, especially Bukhara and Balkh around the 5th century AH in order to avoid usury in borrowing. Many of the rich when it is not willing to lend money without any remuneration they receive. While many of the borrowers are not able to pay off debts due in return they have to pay along with money borrowed. On the other hand benefits granted on the basis of borrowing money, according to scholars of fiqh including usury. So to avoid usury, the community of Bukhara and Balkh formatting a form of trading known as alWafa` Baiu. For todays economic context BaiulWafa` should be considered to be applied in the activities muamalatMuslim community, especially in Indonesia as a substitute for Pawn institutions that practice during this conflict with Rahan outlined by the texts, especially in terms of taking advantage of pledges by the lien holderÂ Baiu al-Wafa` muncul pertama kali di Asia Tengah khususnya Bukhara dan Balkh sekitar abad ke 5 Hijriyah dalam rangka menghindari terjadinya riba dalam pinjammeminjam. Banyak di antara orang kaya ketika itu tidak mau meminjamkan uangnya tanpa ada imbalan yang mereka terima. Sementara banyak pula para peminjam uang tidak mampu melunasi hutangnya akibat imbalan yang harus mereka bayarkan bersamaan dengan uang yang dipinjam. Di sisi lain imbalan yang diberikan atas dasar pinjam-meminjam uang itu menurut ulama fikih termasuk riba. Maka untuk menghindarkan diri dari riba, masyarakat Bukhara dan Balkh memformat suatu bentuk jual beli yang dikenal dengan Baiu al-Wafa`. Untuk konteks ekonomi dewasa ini, Baiul Wafa` patut dipertimbangkan untuk diterapkan dalam aktivitas muamalat masyarakat Muslim khususnya di Indonesia sebagai pengganti institusi Gadai yang praktiknya selama ini bertentangan dengan Rahan yang digariskan oleh nash terutama dalam hal mengambil manfaat dari barang gadaian oleh pemegang gadai.